Quality characteristics and volatile profiles of giant salamander (Andrias davidianus) meat during the air frying process - Luo, Zhixin; Cheng, Kaiqi; Li, Haicheng; Yang, Hui; Ran, Yecheng; Yang, Zhou; Su, Wen; Xi, Linjie; Jin, Wengang; Abd El-Aty, A. M.; Gao, Ruichang (Frontiers in Nutrition, 2026)
IntroductionThis study investigated the effects of air frying duration on the texture, color, and flavor characteristics of Andrias davidianus meat slices.MethodsMeat slices were air fried at 180 °C for 0–20 min. Quality attributes and volatile compounds were analyzed using HS-GC-IMS and multivariate statistical analysis.ResultsWith increasing frying durations, the shear force and a* values significantly increased (P < 0.05), whereas the yield and L* values decreased (P < 0.05), and the b* value peaked at 15 min. A total of 48 volatile compounds, including aldehydes, ketones, esters, acids, alcohols, terpenes, and sulfides. The aldehyde and ketone contents increased with frying durations, whereas the ester and sulfide contents decreased, and the acid contents increased and then decreased. Principal component analysis (PCA) effectively distinguished samples at different frying stages, and orthogonal partial least squares discriminant analysis (OPLS-DA) identified 22 key volatiles with variable importance in projection (VIP) > 1. Relative odor activity value (ROAV) analysis further revealed 15 odor-active compounds (ROAVs = 1), among which 1-octen-3-ol, hexanal, ethyl 2-methylpropanoate, methyl benzoate, and diallyl disulfide were key aromatic substances.ConclusionsAir frying at 180 °C for 10–15 min resulted in more desirable quality and flavor characteristics, providing guidance for the development of ready-to-eat giant salamander meat products.